2020
DOI: 10.3390/ijerph17030833
|View full text |Cite
|
Sign up to set email alerts
|

“Our Tradition Our Enemy”: A Qualitative Study of Barriers to Women’s HIV Care in Jimma, Southwest Ethiopia

Abstract: Evidence exists that suggests that women are vulnerable to negative HIV treatment outcomes worldwide. This study explored barriers to treatment outcomes of women in Jimma, Southwest Ethiopia. We interviewed 11 HIV patients, 9 health workers, 10 community advocates and 5 HIV program managers from 10 institutions using an in-depth interview guide designed to probe barriers to HIV care at individual, community, healthcare provider, and government policy levels. To systematically analyze the data, we applied a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…One explanation for this disparity is that PLHIV may face different barriers depending on their socioeconomic background. 21 , 22 Poor women living with HIV in Ethiopian cities, for example, reported selling antiretroviral drugs to cover ART-related cost. 22 In contrast, PLHIV from wealthy backgrounds may have faced barriers to accessing HIV testing and treatment, such as stigma and discrimination, lack of private clinics, and concerns about potential loss of social status and community standing if community members learned about their HIV positive status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this disparity is that PLHIV may face different barriers depending on their socioeconomic background. 21 , 22 Poor women living with HIV in Ethiopian cities, for example, reported selling antiretroviral drugs to cover ART-related cost. 22 In contrast, PLHIV from wealthy backgrounds may have faced barriers to accessing HIV testing and treatment, such as stigma and discrimination, lack of private clinics, and concerns about potential loss of social status and community standing if community members learned about their HIV positive status.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 Poor women living with HIV in Ethiopian cities, for example, reported selling antiretroviral drugs to cover ART-related cost. 22 In contrast, PLHIV from wealthy backgrounds may have faced barriers to accessing HIV testing and treatment, such as stigma and discrimination, lack of private clinics, and concerns about potential loss of social status and community standing if community members learned about their HIV positive status. 23 Another explanation for wealth disparities in attaining the 90s could be the World Health Organization (WHO) 2016 recommendation for universal HIV testing and treatment (UTT).…”
Section: Discussionmentioning
confidence: 99%
“…These accessibility dimensions were reflected in the fact that participants could afford to buy herbal medicines at public markets or via online sources, or were able to make traditional medicines themselves out of roots, leaves and bark of plants which they could easily find, or via care sought from local traditional healers. Although there have never been studies exploring the influence of packaged herbal medicines and traditional medicines on the access of MLHIV to HIV care services or treatment, some previous studies involving people living with HIV (PLHIV) in general have suggested that the use of traditional medicines has influenced adherence to ART (52-55). Our findings also suggest that peer influence played an important role in the use of these packaged herbal and traditional medicines by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in Tanzania, Uganda, and Zambia reported on consultation with a TH as a factor associated with poor ART adherence [ 30 ]. Only a recent study in Ethiopia by Gesesew and colleagues, which explored the access of women living with HIV (WLHIV) to HIV care services, reported on the restrictions of THs towards the use of ART as barriers for the women to accessing HIV care services [ 35 ]. This paper aimed to fill this gap in knowledge by exploring the cultural practice of the use of TMs for HIV treatments in Belu, and family and social influence on HIV treatment of PLHIV.…”
Section: Introductionmentioning
confidence: 99%